Cold exposure enhances fat utilization but not non-esterified fatty acids, glycerol or catecholamines availability during submaximal walking and running - Dominique Daniel Gagnon; Hannu eRintamäki; Hannu eRintamäki; Sheila eGagnon; Stephen S Cheung; Karl-Heinz eHerzig; Karl-Heinz eHerzig; Katja ePorvari; Heikki eKyröläinen (Frontiers in Physiology, 2013)
Cold exposure modulates the use of carbohydrates and fat during exercise. This phenomenon has mostly been observed in controlled cycling studies, but not during walking and running when core temperature and oxygen consumption are controlled, as both may alter energy metabolism. This study aimed at examining energy substrate availability and utilization during walking and running in the cold when core temperature and oxygen consumption are maintained. Ten lightly clothed male subjects walked or ran for 60-min, at 50% and 70% of maximal oxygen consumption, respectively, in a climatic chamber set at 0°C or 22°C. Thermal, cardiovascular, and oxidative responses were measured every 15-min during exercise. Blood samples for serum non-esterified fatty acids, glycerol, glucose, beta-hydroxybutyrate, plasma catecholamines, and serum lipids were collected immediately prior, and at 30- and 60-min of exercise. Skin temperature strongly decreased while core temperature did not change during cold trials. Heart rate was also lower in cold trials. A rise in fat utilization in the cold was seen through lower respiratory quotient (-0.03 ± 0.02), greater fat oxidation (+0.14 ± 0.13 g•min-1) and contribution of fat to total energy expenditure (+1.62 ± 1.99 kcal•min-1). No differences from cold exposure were observed in blood parameters. During submaximal walking and running, a greater reliance on derived fat sources occurs in the cold, despite the absence of concurrent alterations in non-esterified fatty acids, glycerol, or catecholamine concentrations. This disparity may suggest a greater reliance on intra-muscular energy sources such as triglycerides during both walking and running.